2022
DOI: 10.3390/nu14153188
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Balance and Carbohydrate Intake of Elite Female Soccer Players during Training and Competition

Abstract: This study examined sweat rate, sweat sodium concentration [Na+], and ad-libitum carbohydrate and fluid intakes in elite female soccer players during training (n = 19) and a match (n = 8); eight completed both for comparisons. Body mass (kg) was obtained before and after exercise to calculate sweat rate. The sweat [Na+] was determined from absorbent patches on the thigh or back. Sweat rate, percentage body mass change, and sweat [Na+] for 19 players during training were 0.47 ± 0.19 L·h−1, +0.19 ± 0.65%, and 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Studies have shown that women generally have lower SR values due to their lower body mass and lower absolute work rates [ 12 , 21 ]. Our results are consistent with the scientific literature, indicating lower values in female soccer players (0.65 ± 0.16 L/h) compared to U23-21 male soccer players (1.14 ± 0.54 L/h), particularly during summer training in both RM (0.72 ± 0.17 L/h vs. 1.34 ± 0.46 L/h) and n-RM (0.68 ± 0.16 L/h vs. 1.46 ± 0.40 L/h).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that women generally have lower SR values due to their lower body mass and lower absolute work rates [ 12 , 21 ]. Our results are consistent with the scientific literature, indicating lower values in female soccer players (0.65 ± 0.16 L/h) compared to U23-21 male soccer players (1.14 ± 0.54 L/h), particularly during summer training in both RM (0.72 ± 0.17 L/h vs. 1.34 ± 0.46 L/h) and n-RM (0.68 ± 0.16 L/h vs. 1.46 ± 0.40 L/h).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the sensation of thirst may not always accurately reflect the body’s fluid needs [ 11 ]. Additionally, the high-intensity nature of soccer, coupled with limited fluid availability during competitions, may increase the risk of dehydration for players [ 4 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pre-session urine osmolarity conveyed that 11/14 players (79%) commenced the training session euhydrated (<700 mOsmol·kg −1 ) [ 54 ], with a mean pre-session urine osmolarity of 453 ± 283 mOsmol·kg −1 . Previous research investigating the pre-exercise hydration status of athletes in a variety of sports is equivocal, with some athletes displaying euhydration pre-exercise [ 65 , 68 , 70 , 71 , 73 , 75 , 77 , 79 , 80 , 90 , 93 , 96 , 97 , 98 , 100 , 102 , 115 ] and others displaying hypohydration pre-exercise [ 62 , 63 , 66 , 72 , 74 , 75 , 76 , 78 , 79 , 80 , 82 , 84 , 88 , 89 , 91 , 92 , 94 , 95 , 101 , 116 ]. Athletes’ hydration status appears to be individualised, as exhibited by the range in values recorded in the present study (150 mOsmol·kg −1 to 1000 mOsmol·kg −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Athletes’ hydration status appears to be individualised, as exhibited by the range in values recorded in the present study (150 mOsmol·kg −1 to 1000 mOsmol·kg −1 ). Indeed, previous research displays high variability among cohorts of athletes [ 62 , 63 , 65 , 66 , 68 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 82 , 84 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 100 , 101 , 115 , 116 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation